Influence of pre-slaughter transportation and capture chase stress on carcass and meat quality of indigenous chicken reared under traditional system in Benin. - BONOU, ASSOUAN GABRIEL; AHOUNOU, GBÊNAGNON SERGE; SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; Arnaud Yetonde Fanou, ANOUMOU JOSEPH; DAHOUDA, MOHAMADOU; DOUGNON, TOSSOU JACQUES; MENSAH, GUY APOLLINAIRE; YOUSSAO ABDOU KARIM, ALASSANE (My University, 2017)
Muscovy ducks reared in Benin have a good growth performance and are very rustic animals. However, these birds’ carcass traits are littleknown. This study aimed to evaluate the body composition of Muscovy ducks reared in South Benin. Thus, data on carcass traits and fifth quarter components were collected from February 07 to April 04, 2018 on 40 Muscovy ducks, including 5 males and 5 females by age class with a total of four age classes. The age 1 was for ducks of 4 to 6 months old, the age 2 for ducks of 6 to 8 months old, the age 3 for birds of 8 to 10 months old and the age 4 for animals older than 10 months. The collected data was analyzed with SAS (Statistical Analysis System, 2013). Means, standard deviations and coefficients of variation were calculated by the procedure Proc meansand the frequenciesby the procedure Procfreq.The live weight at slaughter, the hot carcass weight, the cold carcass weight, the body components weight of males were higher (p<0.001) than those of females. The hot carcass yield, the cold carcass yield and the percentages of carcass components and of the fifth quarter had this same trend. On the contrary, the abdominal fat weight of males was lower than that of females (p<0.01). This study also revealed that the live weight at the slaughter, the hot carcass weight, the cold carcass weight and the carcass components weight increased gradually with age (p<0.001). However, age has no effect on the thighs, liver and head percentages (p>0.05). The principal components analysis revealed three groups of traits: the group 1 concerns quantitative traits, the group 2, organ percentages considering carcass weights, and the group 3, carcass yields at slaughter. The animal age at slaughter, the animal live weight at slaughter, the hot carcass weight, the cold carcass weight, the carcass cuts weight and the fifth quarter components weight were positively correlated with each other and negatively correlated with the percentages of the carcass cuts and of viscera. In sum, the body composition of Muscovy ducks varies according to the sex and animal age at slaughter.
Keywords: Muscovy duck; carcass; weight; Benin.